Penerapan Good Corporate Governance (GCG) terhadap Kinerja PT. Bank Rakyat Indonesia (Persero) Tbk - Friska Olavia Sitorus; Imamah Khairiyah; Sakinah Jahrani Nasution (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Good Corporate Governance that is applied in the banking world will support the implementation of banking operations, where banking is an institution that is trusted by the community where funds are entrusted to the manager, so that management must be very careful in managing risks, in order to get a positive image from customers. Moreover, the task of banking in general is to trust in collecting funds and storing funds. This study aims to determine how good corporate governance is applied to financial performance at PT. Bank Rakyat Indonesia. Keywords: good corporate governance, performance.